Diffusion tensor imaging and fibre tractography of leukoaraiosis - Hanapi, Fatin Ayuni (Universiti Sains Malaysia, 2016)
Diffusion tensor imaging (DTI) is an important technique in magnetic resonance imaging (MRI) which is utilized in brain imaging . DTI detects and measures mobility of water molecules in biological cells. It also provides scalar indices which is mean diffusivity (MD) and fractional anisotropy (FA). Futhermore, the neuron fibre bundles can be visualized by using special technique in DTI, namely fibre tractography. Leukoaraiosis is a type of abnormal appearance in the white area of human brain and this region appears hyperintense on T2- weighted and fluid attenuation inversion recovery (FLAIR) magnetic resonance (MR) images. It is commonly found in normal elderly which is related to ischemic stroke and cerebrovascular disease. The objective of this study is to reconstruct the DTI parametric maps and fibre tractography and measure the DTI values and number of fibres in corpus callosum(CC) and corticospinal tract(CST). It is also to compare the FA and MD values obtained between right and left of CST. The subject had leukoaraiosis at right side frontal white matter region and data analysis was acquired by using commercial software, NordicICE Version 2.3.13. MD. FA, and colour coded FA maps and fibre tractography were constructed. Region of interest were located at corpus callosum and at right and left side of corticospinal tract. For CST no differences was found for MD and FA values at both sides. Fibre tractography showed right CST have 17.4% lesser number of fibers compared to left CST. Whereas, for corpus callosum the MD value is 96.52 ± 30.34 and FA is 0.56 ± 0.19 with 11451 number of fibres. In conclusion, DTI parametric maps and fibre tractography has been reconstructed, DTI values and number of fibres in CC and CST also can be measured. The comparison of DTI values between right and left side of CST was successfully obtained.